POETRY AS SOCIAL CRITISM DURING THE GUIDED DEMOCRACY ERA IN INDONESIA 1959-1966: Puisi sebagai Kritik Sosial pada Masa Demokrasi Terpimpin di Indonesia 1959-1966 - Sayfullah, Muhammad Zaki; Muzakki Bashori (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines the role of poetry as a medium of social criticism during the Guided Democracy Period in Indonesia from 1959 to 1966. Amidst political instability, authoritarian governance under President Soekarno, and widespread sosial inequality, poetry emerged as a tool for resistance and public conscience. The research aims to explore how Indonesian poets employed literary expression to critique oppressive power structures and advocate for the marginalized. Using the historical research method, this study analyzes primary sources, including poems written by Agam Wispi, S. Anantaguna, Goenawan Mohamad, and Taufiq Ismail, along with historical documents and secondary literature. The findings reveal the poets affiliated with different ideological groups, such as Lekra and Manikebu, produced diverse yet convergent forms of social criticism through their works. These poems address themes of land injustice, political cencorship, and social disparity. The study highlights poetry not only as an artistic expression but also as a historical document that captures the zeitgeist of a politically turbulent era. The novelty of this research lies in its interdisciplinary approach, combining literary analysis with historiography to offer a broader understanding of poetry as both cultural artifact and historical resistance. This underscores the relevance of literature as a powerful tool for political expression and social advocacy in Indonesia’s democratic history.